Increased expression of secretory actin-binding protein on human spermatozoa is associated with poor semen quality - Čapková, Jana; Elzeinová, Fatima; Novák, Petr (Human reproduction, 2007)
BACKGROUND: Antibodies to human sperm are useful diagnostic reagents for detection of changes in sperm protein expression and their relationship with sperm defects and male infertility. The specificity of Hs-16 monoclonal antibody (mAb) and the localization and frequency of the occurrence of Hs-16-recognized protein on human spermatozoa were investigated. METHODS: Samples from 30 fertile men with normal spermiograms and 30 men with pathological spermiograms were studied. The specificity of Hs-16 mAb was analysed by the western blotting technique and matrix-assisted laser desorption/ionization mass spectrometry. Indirect immunofluorescence with Hs-16 antibody was used to test sperm ejaculates. RESULTS: The Hs-16 antibody detected a human sperm and seminal plasma protein, which was determined to be secretory actin-binding protein (SABP). This specificity was also verified by co-localization of SABP and actin on spermatozoa with Hs-16 and anti-actin antibodies, and partial co-localization of these proteins was found. SABP was localized on the sperm tail, mainly in the midpiece of the tail. Other parts of spermatozoa were labelled with lower frequency. A significant difference was found in SABP labelling between men with normal spermiograms and donors with asthenozoospermia or oligoasthenoteratozoospermia (both P < 0.01), and asthenozoospermia versus oligoasthenoteratozoospermia (P < 0.05). Increased expression of SABP was observed in men with pathological spermiograms. CONCLUSIONS: Hs-16 antibody reacts specifically with SABP. SABP can serve as a marker of defective sperm and may be associated with fertility failure.
Keywords: financování organizované; dospělí; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; spermie; Adult; Spermatozoa; fluorescenční protilátková technika nepřímá; mikrofilamentové proteiny; Antibodies, Monoclonal; lidé; Financing, Organized; Male; aktiny; Actins; monoklonální protilátky; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Fluorescent Antibody Technique, Indirect; mužské pohlaví; Microfilament Proteins; Humans